Critical events leading to cellular mortality of yeast cells following hydrostatic pressure treatment. Issue 2 (3rd April 2019) - Hamada, Kazuhiro; Miwa, Akihisa; Takahashi, Ukyo; Iwahashi, Hitoshi
ABSTRACT: Hydrostatic pressures of 40–150 MPa are sub-lethal conditions for yeast cells. On exposure to this pressure range, damaged yeast cells will attempt to recover, but a critical cellular event may ultimately lead to cell mortality. We employed yeast strains whose cellular organelles were labeled with green fluorescent protein to investigate this critical event. We were able to visualize the nuclear membrane, nucleus, endoplasmic reticulum, Golgi body, and plasma membranes. Of the cellular organelles tested, the nuclear membrane was the weakest, displaying damage following only 50 MPa of pressure. This nuclear membrane rupture correlated with cellular viability. Thus, we hypothesize that nuclear membrane damage is the critical event leading to cellular mortality of yeast cells following hydrostatic pressure treatment.